2008
DOI: 10.1139/h08-080
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled crossover trial of the effect of ginseng consumption on the immune response to moderate exercise in healthy sedentary men

Abstract: Ginseng is a popular herbal remedy that is reputed to increase resistance to stress and improve immune function. Regular exercise results in acute physiologic stress that affects the immune response. This study was conducted to investigate the effects of daily consumption of a standardized ginsenoside-containing North American ginseng (Panax quinquefolius) extract on immune function before, during, and after a moderate-exercise protocol in healthy sedentary men. Ten healthy males were randomized to receive eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
0
18
1
Order By: Relevance
“…4). These results differ somewhat from those of a study we conducted in sedentary young men [23], in which ginseng consumption reduced peripheral blood concentrations of CD8+ T cells but had no effect on CD28+ or CD45RO+ cells, or neutrophil function. These differences suggest that the effects of ginseng on the immune response to exercise may differ between men and women, an issue that deserves further study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…4). These results differ somewhat from those of a study we conducted in sedentary young men [23], in which ginseng consumption reduced peripheral blood concentrations of CD8+ T cells but had no effect on CD28+ or CD45RO+ cells, or neutrophil function. These differences suggest that the effects of ginseng on the immune response to exercise may differ between men and women, an issue that deserves further study.…”
Section: Discussioncontrasting
confidence: 99%
“…T cells, B cells, NK cells) measured at rest among endurance athletes [22]. In a randomized, controlled, crossover trial of North American ginseng consumption among healthy sedentary young men, we found that ginseng consumption for 35 days reduced peripheral blood CD8+ T cell concentrations and increased ex vivo IL-2 production, but otherwise had a limited effect on the immune response to exercise [23]. The present study was conducted to investigate the effects of daily consumption of a standardized ginsenoside-containing North American ginseng (Panax quinquefolius) extract on immune function in a non-athletic population of women before, immediately after, and during recovery from an acute physiological stress (a moderate exercise protocol).…”
Section: Introductionmentioning
confidence: 82%
“…These results suggest that FRG-E has potent immunomodulatory properties by enhancing macrophage function, followed by the contribution of the potent anti-tumor activity of FRG in vivo. It is well documented that several ginsenosides from ginseng may contribute to the activation of systemic and mucosal immunity in rats by oral administration [27]. In addition, our previous data revealed that FRG-E seemed to increase anti-tumor activity compared to NFRG-E in a lung metastasis model of colon 26-M3.1 carcinoma cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…fl Proliferative response of lymphocytes to mitogens (19) › Number of circulating neutrophils and monocytes (52) fl Number of circulating lymphocytes and T-lymphocyte › Monocyte and neutrophil phagocytosis (38) › CD4 + /CDB + ratio after strenuous and prolonged exercise fl Nasal neutrophil phagocytic capacity (transient suppression) (27) › Levels of pro-inflammatory cytokine IL-6 (35,38) fl Expression of toll-like receptors (35) › Levels of anti-inflammatory cytokines IL-10 und IL-1ra › Cortisol production fl Levels of TNFa › CRP level (35) Lipolysis induction fl Th1/Th2 ratio (150) fl Nasal and salivary IgA level (27) fl Macrophage major histocompatibility complex class II expression (27,35,151) › T-memory (CD45RO + ) and T-nai¨ve (CD45RA + ) cell counts (154,156) › CD45RO + /CD45RA + ratio (154,156) fl -Alteration of regulatory mechanism (155) fl Levels of biomarkers that are used to assess systemic inflammation (mitogen-stimulated inflammatory cytokine production, skeletal muscle inflammatory protein content, adipokine production, serum levels at CRP) (35) fl Exercise-induced IL-6 mRNA response after 10 weeks of training (untrained young men) (157) fl Systemic concentrations of IL-6 in elderly people at risk for disability (158) Not suppress the salivary IgA response or alter cortisol secretion (159) CRP, C-reactive protein; NK, natural killer; Th, T helper; ›, increase; fl, decrease.…”
Section: Physical Activity: Immune Function: Infection: Nutritionmentioning
confidence: 99%
“…(CD3+ , CD4+ , CD16+ and CD20+ ) counts, lymphocyte proliferation or neutrophil oxidative burst (150) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%